Retrograde intubation as a rescue strategy in a patient with distorted laryngeal anatomy after tracheal resection and anastomosis: A case report - Sivalakshmi Rajendran; Rajesh Kumar Kodali; Mahesh Vakamudi; Aruna Parameshwari (Journal of Perioperative Practice, 2026)
This case report describes the anaesthetic management of a 62-year-old female with recurrent papillary carcinoma thyroid presenting with tracheal invasion and significant airway narrowing. This case underscores the implementation of elective tracheostomy and effective retrograde endotracheal intubation following unsuccessful video laryngoscopic attempts due to altered laryngeal anatomy, consequently ensuring safe perioperative airway management.